An XML model that enables the development of complex order sets by clinical experts. - Del Fiol, G. (IEEE Transactions on information technology in biomedicine)
Medication errors are significant and well-known problems in health care. Despite the evidence supporting the use of computerized physician order entering (CPOE) to help reduce medication errors, only a small number of hospitals in the U.S. have successfully implemented a CPOE system. Different authors have indicated that the utilization of order sets derived from best-practice standards can reduce medication errors and improve physicians' acceptance of CPOE systems. However, a variety of issues related to the development and continuous maintenance of best-practice order sets still need to be understood. This paper presents a model that supports an order set development process driven by clinical experts. Model requirements and details are presented and discussed.